Long-term outcomes for children with disability and severe acute malnutrition in Malawi. Issue 10 (7th October 2020) - Lelijveld, Natasha; Groce, Nora; Patel, Seema; Nnensa, Theresa; Chimwezi, Emmanuel; Gladstone, Melissa; Mallewa, Macpherson; Wells, Jonathan; Seal, Andrew; Kerac, Marko
Abstract : Introduction: Severe acute malnutrition (SAM) and disability are major global health issues. Although they can cause and influence each other, data on their co-existence are sparse. We aimed to describe the prevalence and patterns of disability among a cohort of children with SAM. Methods: A longitudinal cohort study in Malawi followed SAM survivors up to 7 years postdischarge. Clinical and anthropometric profiles were compared with sibling and community controls. Disability at original admission was identified clinically; at 7-year follow-up a standardised screening tool called 'the Washington Group Questionnaire' was used. Results: 60/938 (6.4%) of admissions to SAM treatment had clinically obvious disability at admission. Post-treatment mortality was high, with only 11/60 (18%) surviving till 7-year follow-up. SAM children with a disability at admission had 6.99 (95% CI 3.49 to 14.02; p<0.001) greater risk of dying compared with children without disability. They were also older, less likely to be HIV positive or have oedema and more severely malnourished. Long-term survivors were more stunted, had less catch-up growth, smaller head circumference, weaker hand grip strength and poorer school achievement than non-disabled survivors. The Washington Group Questionnaire confirmed disability in all who had been identified clinically, and identified many who had not been previously flagged. Conclusion: Disability is common among children affected by SAM. Those with disability-associated SAM have greatly increased risk of dying even if they survive the initial episode of malnutrition. Survivors have poorer growth, physical strength and school achievement. To enable all children to survive and thrive post-SAM, it is vital to focus more on those with disabilities. SAM treatment programmes should consider using not just clinical assessment but structured assessments to better identify at-risk individuals as well as understand the population of children for which they are developing services.